Crosstalks between mTORC1 and mTORC2 variagate cytokine signaling to control NK maturation and effector function - Fangjie Wang; Meng Meng; Banghui Mo; Yao Yang; Yan Ji; Pei Huang; Wenjing Lai; Xiaodong Pan; Tingting You; Hongqin Luo; Xiao Guan; Yafei Deng; et al. (Nature Communications, 2018)
The metabolic regulator protein family, mTOR, regulate natural killer (NK) cell development and function, but the underlying mechanism is unclear. Here, the authors show that Raptor/mTORC1 and Rictor/mTORC2 form a feedback crosstalk network to variegate cytokine and cellular signaling and modulate NK maturation and effector functions.